State-level differentials in COVID-19 fatality: exploring age and sex disparities in Malaysia's pandemic experience - Jane K. L. Teh; Kok Lay Teo; David A. Bradley; Jack Bee Chook; Woo Teck Ang; Suat-Cheng Peh (Springer, 2024)
Abstract Issue COVID-19 has resulted in mortality worldwide and exposed vulnerabilities in public health systems. Although countries have since transitioned to the endemic phase, it is nonetheless important to identify inequities within populations to improve public health strategies in light of another health crisis. Purpose This study aims to offer deeper insights into the sex and age differentials in COVID-19 fatality across different states in Malaysia, from the pandemic's start to the country's transition to the endemic phase. Methodology Analyses utilized data on the number of COVID-19 cases and deaths in Malaysia from January 2020 until April 2022. Case fatality rate (CFR) was computed for each state based on sex and age groups, for four periods (January-December 2020, January-June 2021, July-December 2021, and January-April 2022). Principal component analysis (PCA) uncovered patterns in the data and produced a multivariate visualization of the COVID-19 fatality within Malaysia. Findings Findings revealed heterogeneity in fatality and identified several vulnerable states, notably in the northern region (Kelantan, Perlis) and on the East Coast (Sabah, Sarawak). A sex disparity was apparent in Kelantan as the CFR among older females was higher than their male counterparts. Sabah exhibited relatively higher CFR among the child population from 2020 to 2021. Implication The findings deepened our understanding of COVID-19 fatality complexity, providing recommendations for Malaysia's government in preparing for future health crises. Malaysia's case study offers lessons on the need to address regional disparities and implement targeted strategies to protect vulnerable subgroups.